Diversitas Perifiton pada Lokasi Pepohonan dan Non Pohon di Wisata Coban Putri Desa Tlekung, Junrejo, Kabupaten Batu, Jawa Timur - AINUL KHATIMAH; Annisa Zakiyah Darojat (JPSL : Jurnal Pendidikan, Sosial dan Lingkungan, 2025)
This study is an exploratory study that illustrates the diversity of periphyton in Coban Putri in Batu Regency dan measures the physical and chemical parameters including temperature, turbidity, light intensity, DO/BOD, nitrat, and orthophosphate. This study was conducted at 4 stations namely NPMA (non pohon mengalir/non tree-flowing), PMA (pohon mengalir/tree-flowing), NPMG (non pohon menggenang/non tree-welled up), and PMG (pohon menggenang/tree-welled up) by brushing epiphyte of periphyton on surfaces of stone and wood. Periphyton was identified by matching the identification book and 23 species were found. The highest periphyton abundance was found at NPMG 14395,16 n/ml. Physical parameters were pH 7,95-8,25, turbidity 5,5-18,6 NTUs, conductivity 0,13-0,14 mS/cm, temperature 20-22oC, and water brightness 5-24 cm. While chemical parameters were DO 4,80-5,30 mg/l, BOD 2,08-6,72 mg/l, nitrat 0,24-0,44 mg/l, and orthophosphate 0,01-0,06 mg/l. The species of periphyton found at 4 stations indicated the highest periphyton diversity at NPMG.